Impactos ambientales generados por la construcción de un muelle para el atraque de buques de transporte de mineral, sobre el sistema marino litoral de Salaverry, mayo – diciembre del 2009. - Montalvo Bonilla, Jorge Luis (2011)
The main objective of this thesis was: To identify environmental impacts in the initial stages of construction and closure of the site of a port project to adopt preventive measures in the construction of a pier or dock alternate transport ships ore in the port of Salaverry, located in the department of La Libertad, the potential construction area is known southern breakwater which is located within the premises of the National Port Company Salaverry (ENAPU) for such a procedure in study identified three (03) sampling stations "A" and "B" adjacent to the docks, and the station "C" located adjacent to the south breakwater for use as benchmarks. The sampling was done periodically fortnight of May, August and November for both surface and bottom. In this study it was determined that the springs are exposed to continuous shipments (Station A and B) are more contaminated by the continuous dredging, merchant ships docking and removal of waste at sea as opposed to the sampling station "C" an area that is undisturbed by human action. In determining the nature of the impact according to the Leopold Matrix was concluded that building a dock at the Port Terminal Salaverry, generate significant positive environmental impact from further consideration due to the benefit of the population, creating jobs as new technologies used now for the shipment of ore as the ore conveyor belt tight contribute much to keep the ecosystem in a sustained manner.